« Séparer l'Église et l'État : L'augustinisme politique selon Arquillière » - Blaise Dufal (L'Atelier du CRH)
The political augustinism' concept, introduced by Arquillière in the 30's, involves a particular conception of Church history and its relations with secular powers. It was built up by neo-thomistic thinkers, who tried to develop an ecclesiological theory compatible with the assertion of lay nation-states. As a distorsion of Augustine's thought, political augustinism enables the limitation of theocratical ideas to medieval doctrines, which are considered as exceptions explained by historical context.